2017
DOI: 10.1002/joc.5013
|View full text |Cite
|
Sign up to set email alerts
|

A regional frequency analysis of precipitation extremes in Mainland China with fuzzy c‐means and L‐moments approaches

Abstract: Owing to their essential influence on human society and natural environment exerted by inducing disasters, such as floods and droughts, further studies on precipitation extremes in China are needed. This study presents the regional frequency and spatial‐temporal patterns of precipitation extremes in China based on a high‐resolution (0.5° × 0.5°) daily precipitation dataset from 1961 to 2013. With fuzzy c‐means, L‐moments methods and other scientific statistical tests, a regional frequency analysis (RFA) is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
2
27
1
1
Order By: Relevance
“…This suggests that satellite-based estimates combined with gauge information would be effective to identify extreme precipitation. Similar results were found by [19] and [37], who showed that post-real-time products agreed well with the gauge-based observations and presented satisfactory performance for China. In addition, [63] compared the performance of TRMM, IMERG-F, and GSMaP-Gauge in Brazil and demonstrated that IMERG-F and GSMaP-Gauge presented better performance in comparison with near-real-time products.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that satellite-based estimates combined with gauge information would be effective to identify extreme precipitation. Similar results were found by [19] and [37], who showed that post-real-time products agreed well with the gauge-based observations and presented satisfactory performance for China. In addition, [63] compared the performance of TRMM, IMERG-F, and GSMaP-Gauge in Brazil and demonstrated that IMERG-F and GSMaP-Gauge presented better performance in comparison with near-real-time products.…”
Section: Discussionsupporting
confidence: 87%
“…The data quality was previously checked by Zhao, Zhu [22] using cross-validation and error analysis. The data have been widely used in climate analysis, numerical model verification, and hydrological studies [23,24].…”
Section: Study Area and Datamentioning
confidence: 99%
“…Regular grid points were created by CMA based on observed precipitation data (six stations inside SRYR and more than 15 stations outside) and a Digital Elevation Model from GTOPO30 (Hutchinson, 1998). The dataset has been widely used in climate analysis, numerical model verification, and hydrological studies (Shi et al, 2017;Wang et al, 2017). The quality of the dataset has been checked by using cross validation and error analysis by Zhao et al (2014).…”
Section: Datamentioning
confidence: 99%